Gerenciamento de recursos hídricos em uma bacia experimental na Amazônia Central - Nascimento, Dênis Aguero do (2019)
This work had as main scope the management of hydrometric data generated in Julian years of 2015 and 2016 in the Experimental Basin of Igarapé Asu (BEIA). It is a site of hydrometeorological research implemented in the middle of the year 2000 and that went through reinstrumentation and optimization of the generation of the hydrometric series from 2015. The area analyzed corresponds to one of the Monitoring Sections of BEIA. The area was estimated at 6.31 km², is of primary forest preserved and is subject to the pulses of the hydrological regime that promotes flooding of the floodplain area. For the best evaluation of the flow rates, the Manning roughness coefficient was determined at the fluviometric point of interest and total pressure series were converted into mH2O to estimate the discharge / discharge ratio. The pluviometric data of the network of stations had their consistency analyzed by the method of Double Mass, indicating little variability of the occurrence of rainfall in the studied area. With the morphometric analysis of the basin, the plain was calculated with 51% of the catchment area, and the plateau with 35%. The surface of the plain is close to the water table, where in the valley bottom regions the soil is characterized by hydromorphy, with rapid saturation in periods of more intense rains, a fact that promotes through the Hortonian flow a rapid hydrological response in the increase of the quota limnimetric, however, with long periods of resection in concentration time. The plateau has an important role in the storage of groundwater, which in later periods maintains the hydraulic dynamics of the drainage network by means of lateral contribution, as well as the supply of the flora of the lower zones. This characteristic caused a deficit in the water table in the studied years, a fact that indicates the susceptibility of the hydrological regime of the BEIA to the rainfall variation, especially in years with more intense El Niño - Southern Oscillation (ENSO) phenomenon, as occurred in 2016. The hydrological investigation indicated an intimate relationship between the saturated zone, the vegetation and the drainage network, varying the runoff coefficient between 0.51 and 0.30 in the studied years, hindering the indirect estimation of evapotranspiration by the calculation of the water balance by the simplified method of the mass continuity